TEACHING-LEARNING WOUND CARE: THE EXPERIENCE OF TRAINEE TEACHERS OF NURSING - Telma Elisa Carraro; Luciara Fabiane Sebold; Silvana Silveira Kempfer; Ariane Thaise Frello; Mariely Carmelina Bernardi (Universidade Federal do Paraná, 2012)
The carrying out of a teaching placement is a requirement for scholarship students of the Coordination for Perfection of Higher Education Staff and the National Council for Scientific and Technological Development. This text aims to relate the experience of teaching-learning wound care, as experienced by four post-graduate students during their teaching placements, in a public higher education institution in the South of Brazil. The placement took place from August to December 2010 in the Basics of Professional Care course, part of the same university's undergraduate nursing course. It was considered an important learning stage in the contexts tutorship in the classroom, and laboratory and hospital practice, where teaching and learning are very closely linked. The experience permitted a widening of understanding concerning nursing training.